2010
DOI: 10.1007/s00415-010-5884-x
|View full text |Cite
|
Sign up to set email alerts
|

Taste function in patients with Parkinson disease

Abstract: Despite the important role of taste function in nutrition and health, little is known about changes in taste function caused by Parkinson disease (PD). The taste function of 31 PD patients and 29 healthy controls was assessed quantitatively using filter paper taste strip tests (TSTs) impregnated with four basic taste qualities at four different concentrations. The mean TST score was significantly lower in PD patients, as a consequence of taste impairment in the female PD patients (it did not differ significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 19 publications
3
18
1
8
Order By: Relevance
“…Taste is a powerful determinant of food choices (Glanz, Basil, Maibach, Goldberg, & Snyder, 1998). Although PD patients may suffer from taste dysfunctions (Cecchini et al, 2014;Deeb et al, 2010;Kashihara, Hanaok, & Imamura, 2011;Kim et al, 2011;Shah et al, 2009;Sienkiewicz-Jarosz et al, 2005), to date no study has evaluated taste before and/or after DBS or correlated it with weight or food habits. Olfactory problems occur in 90% of early-stage PD patients, and can precede the onset of motor symptoms by years (Doty, 2012).…”
Section: Sensory Perception: Taste and Olfactionmentioning
confidence: 98%
“…Taste is a powerful determinant of food choices (Glanz, Basil, Maibach, Goldberg, & Snyder, 1998). Although PD patients may suffer from taste dysfunctions (Cecchini et al, 2014;Deeb et al, 2010;Kashihara, Hanaok, & Imamura, 2011;Kim et al, 2011;Shah et al, 2009;Sienkiewicz-Jarosz et al, 2005), to date no study has evaluated taste before and/or after DBS or correlated it with weight or food habits. Olfactory problems occur in 90% of early-stage PD patients, and can precede the onset of motor symptoms by years (Doty, 2012).…”
Section: Sensory Perception: Taste and Olfactionmentioning
confidence: 98%
“…More recently, Moberg et al [13] noted that only 24 % of 56 PD patients could detect the bitter taste of phenylthiocarbamide (PTC), as compared to 75 % of 20 healthy controls. Kim et al [14] found a marginal decrease in identification performance of 15 women with PD relative to 14 female controls when the data were combined across sweet, sour, bitter and salty tastants. However, the effects were not significant when any one taste quality was assessed alone.…”
Section: Introductionmentioning
confidence: 98%
“…The small number of PD patients involved in this group may explain the results. Kim et al (7) denied the correlation with age, duration or severity of the disease, cognitive function or olfactory function in patients with PD. The majority of reports indicate that smell impairment does not correlate with disease severity and duration (1,3,13,14).…”
Section: Discussionmentioning
confidence: 99%
“…The determined frequencies of smell impairment vary among reports based on the method of evaluation (i.e., psychophysical "Sniffin' Sticks" testing vs. electrophysiologic testing). Taste impairment has also been reported in patients with PD, but less frequently and with contradictory results (5)(6)(7). Abnormal taste includes reduced, sensitive and altered sensation and taste perception.…”
Section: Introductionmentioning
confidence: 99%